BREXIT REFERENDUM OF EUROPEAN UNION - Laode Muhamad Fathun (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2020)
This paper describes the phenomenon Brexit or Britain Exit on the future of EU regionalism and its impact on Indonesia. This paper will explain in detail the reason for the emergence of a number of policies Brexit. Brexit event caused much speculation related to Brexit in the European Union. The policy is considered full controversial, some experts say that Brexit in the European Union (EU) showed the independence of Britain as an independent state. Other hand, that Britain is the "ancestor" of the Europeans was struck with the release of the policy, meaning European history can not be separated from the history of Britain. In fact the above reasons that Britain came out associated with independence as an independent state related to EU policies that are too large, as a result of the policy model is very holistic policy while Britain desire is wholistic policy, especially in the economic, political, social and cultural. In addition, the geopolitical location of the EU headquarters in Brussels who also became the dominant actor in a union policy that demands as EU countries have been involved in the formulation of development policy, including controversial is related to the ration immigrants. Other reason is the prestige associated with the currency. Although long since Britain does not fully adopt the EU rules but there is the possibility in the EU currency union can only occur with the assumption that the creation of functional perfect integration.